Da invisibilidade à escuta ativa: diálogo com os agentes escolares de uma Escola Municipal de Educação Infantil da cidade de São Paulo - Ferrara, Teresa Andréa (2023)
In the current perspective of Early Childhood Education in the city of São Paulo, all professionals working in the Early Childhood Education Centers and the Municipal School of Early Childhood Education are considered childhood educators who must welcome children and their families, as well as organize the time, spaces and materials for babies and children to experience proposals that consider games, interactions, multiple languages, discoveries, curiosity, raising hypotheses, which are respected according to their rhythms and needs. In this context, the Support Team plays a fundamental role, collaborating with the organization of these environments and actions involving babies and children. During the career as student and professional in Education, it was observed the daily Support Team relationship, which is how this research came about, with the focus on School Agents. This study has the general objective of analyzing how school agents understand their work with 4 and 5-year-old children attended at a Municipal School of Early Childhood Education and, as specific objectives, to identify the evidence about the conception of childhood and child that are underlying in their testimonies, to understand how and if life experiences influence the work of school agents with children, identify when school agents encounter greater difficulties in their daily lives with children These objectives arose from the need to know who are the school agents working in an Early Childhood Education School and to know their professional trajectories with the intention of raising evidence for a future continuing education, considering their real needs. The research followed the principles of the qualitative approach, and a semi-structured interview was used to obtain information. The results confirmed the importance of knowing and listening to school agents life stories in order to identify their training needs, which scarcely differ from the demands of other professionals in the researched unit: a) to know how four/five-year-old children develop; b) understand how to deal with relational conflicts that occur in daily lives of the children; and c) how to provide quality care to children targeted by Special Education